UMPBot competed in ROBOCON 2018 - Nur Laila, Afandi (2018)
Kuala Lumpur, 22nd April – A group of students from Faculty of Manufacturing Engineering, Faculty of Electrical and Electronics Engineering and Faculty of Mechanical Engineering took three months to create a robot and competed in ROBOCON 2018 that was held at Seri Sarjana Hall, UNITEN, Bangi.